Molecular phylogenetics and taxonomy of dwarf hamsters Cricetulus Milne-Edwards, 1867 (Cricetidae, Rodentia): description of a new genus and reinstatement of another - Lebedev, V.s.; Bannikova, A.a.; Neumann, K.; Ushakova, M.v.; Ivanova, N.v.; Surov, A.v. (Zootaxa, 2018)
The taxonomy of the genus Cricetulus has been controversial. The phylogenetic relationships both within the genus and among Cricetulus lineages and other genera were examined using a set of five nuclear and two mitochondrial genes. The results demonstrate that Cricetulus in its current treatment is a polyphyletic assemblage because the subgenus Urocricetus is phylogenetically unrelated to all other Cricetulus and is a distant sister group to Phodopus. The grey hamster (C. migratorius) proved to be closer to Cricetus and Allocricetulus than to Cricetulus proper, which includes C. barabensis C. sokolovi and C. longicaudatus. Based on these results Urocricetus is elevated to the rank of a full genus and a new genus Nothocricetulus gen.nov. is described for the grey hamster.